Sexuality and Transgender Identity Through the PERWAKOS Community : Transgender Surabaya Association - Paramita, Fransisca Benedicta Avira Citra; Ramadhani, Hetti Sari; Putri, Sasmita Aprilia (Kirana Publisher (KNPub), 2025)
The emergence of transgender groups living and living around society is often considered a threat that is a societal disease. The problem of transgender people in Indonesia has always been associated with problems that are then linked by religion and position in society. In the context of cultural society in Indonesia, gender differences and sexual diversity, including transgender and transsexual, can also be said to be gender diversity in Indonesia. This study uses a qualitative method with a descriptive type of research. The result of this research is that PERWAKOS (Surabaya City Waria Community) strives to provide a place and more attention for transvestites to be able to feel accepted in society.